1998
DOI: 10.1007/s002340050684
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced magnetisation transfer MRI in metastatic lesions of the brain

Abstract: Our purpose was to compare prospectively the sensitivity of contrast-enhanced magnetisation transfer (MT) MRI and gradient-echo (GE) T1-weighted images in metastatic disease of the brain. We studied 52 patients with brain metastases, using conventional T1-weighted GE and MT spin-echo (SE) images after the same standard dose of gadolinium. Axial 5-mm reconstructions of GE data were compared with 5-mm MT images in the same plane. Metastases were counted independently by two neuroradiologists. In 12 patients (23%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Although magnetization transfer (MT) techniques [26,27] were not employed in this study, future work might usefully be aimed at assessing the bene®ts of combining this technique with the use of low dose (0.05 mmol/kg) gadobenate dimeglumine. In this regard, a recent study on a mixed lesion population has suggested that T1wSE imaging with MT and 0.05 mmol/kg of a conventional gadolinium agent can replace standard dose T1wSE imaging without MT, at least for the imaging of meningioma [28].…”
Section: Discussionmentioning
confidence: 98%
“…Although magnetization transfer (MT) techniques [26,27] were not employed in this study, future work might usefully be aimed at assessing the bene®ts of combining this technique with the use of low dose (0.05 mmol/kg) gadobenate dimeglumine. In this regard, a recent study on a mixed lesion population has suggested that T1wSE imaging with MT and 0.05 mmol/kg of a conventional gadolinium agent can replace standard dose T1wSE imaging without MT, at least for the imaging of meningioma [28].…”
Section: Discussionmentioning
confidence: 98%
“…166 Meningiomas were found to have, on average, higher MTR values than other tumors, and soft tumors were found to have lower MTR values than hard tumors. 166 The application of an MT pulse to postcontrast T1-weighted images enabled a higher number of lesions to be detected in patients with brain metastases than did plain T1-weighted images, 167,168 with a sensitivity similar to that achieved with administration of a triple dose of Gd.…”
Section: Tumorsmentioning
confidence: 99%
“…MT images were acquired using a spin echo sequence [TR/TE = 5000/8.5 ms, with or without saturation (10 Gaussian pulses of 5 ms, interpulse delay = 300 ms, Figure 2. T 2 -weighted (TE = 75ms) longitudinal follow-up (10,12,14,18 and 21 days after inoculation) of a C6 glioma (pointed out by arrows) and the corresponding histology section at the end point. The presence of a large necrotic core does not allow a perfect slicing and explains the burst observed on the section.…”
Section: Animal Modelmentioning
confidence: 99%